2004
DOI: 10.1074/jbc.m407286200
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin Mediates Ca2+ Sensitivity of Sodium Channels

Abstract: Ca2؉ has been proposed to regulate Na ؉ channels through the action of calmodulin (CaM) bound to an IQ motif or through direct binding to a paired EF hand motif in the Na v 1 C terminus. Mutations within these sites cause cardiac arrhythmias or autism, but details about how Ca 2؉ confers sensitivity are poorly understood. Studies on the homologous Ca v 1.2 channel revealed non-canonical CaM interactions, providing a framework for exploring Na ؉ channels. In contrast to previous reports, we found that Ca 2؉ doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
184
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(205 citation statements)
references
References 43 publications
19
184
2
Order By: Relevance
“…2, B and C) is consistent with numerous studies showing that mutations in the two cytoplasmic domains have concordant effects on the voltage dependence of inactivation, and suggests functional interaction between these regions (9, 29 -31). Moreover, evidence has accumulated in support of interactions between CaM, the C terminus, and the DIII-DIV linker (13,24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2, B and C) is consistent with numerous studies showing that mutations in the two cytoplasmic domains have concordant effects on the voltage dependence of inactivation, and suggests functional interaction between these regions (9, 29 -31). Moreover, evidence has accumulated in support of interactions between CaM, the C terminus, and the DIII-DIV linker (13,24).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the DIII-DIV linker has recently been implicated as a site for CaM interaction (13,14,24). Moreover, it has been proposed that CaM is required to stabilize the interaction of the C terminus with the DIII-DIV linker (13).…”
Section: A Cam-binding Domain In the Diii-div Linker Has Correspondinmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical Evidence for an H1/H4 Hydrophobic InterfaceThe predicted EF-hand pair in the Na V 1.5 COOH terminus contains a single tryptophan, Trp 1798 , which is important not only because our model predicts it to be integral to the hydrophobic interface but also because its intrinsic fluorescence can be used to probe and report the nature of the environment in which it is located (13,24,25). We thus prepared a GST fusion protein consisting of residues predicted to form the EF-hand pair (residues 1786 -1863) and carried out experiments using Trp 1798 as a reporter of its environment.…”
Section: Thermodynamic Cycle Analysis Is Consistent With Predictedmentioning
confidence: 99%
“…Inherited mutations of the III/IV linker in the cardiac Na ϩ channel can disrupt fast inactivation, resulting in sustained current (I SUS ), which can cause long QT syndrome variant 3 (5). However, the Na V 1.5 COOH terminus also has been shown to play a role in inactivation both through chimeric studies (7), through the characterization of several disease-linked mutations found in the C terminus (8 -11), and by direct biochemical evidence for COOH terminus interactions with the cytoplasmic peptide that links domains III and IV of the ␣ subunit (III-IV linker) (12,13). …”
mentioning
confidence: 99%